Kinematic strategies for obstacle-crossing in older adults with mild cognitive impairment - Lu, Shiuan-Huei; Kuan, Yi-Chun; Wu, Kuan-Wen; Lu, Hsuan-Yu; Tsai, Yu-Lin; Chen, Hsiang-Ho; Lu, Tung-Wu (Frontiers in Aging Neuroscience, 2022)
Introduction: Mild cognitive impairment (MCI) is considered a transitional stage between soundness of mind and dementia, often involving problems with memory, which may lead to abnormal postural control and altered end-point control when dealing with neuromechanical challenges during obstacle-crossing. The study aimed to identify the end-point control and angular kinematics of the pelvis-leg apparatus while crossing obstacles for both leading and trailing limbs. Methods: Twelve patients with MCI (age: 66.7±4.2 y/o; height: 161.3±7.3 cm; mass: 62.0±13.6 kg) and twelve healthy adults (age: 67.7±2.9 y/o; height: 159.3±6.1 cm; mass: 61.2±12.0 kg) each walked and crossed obstacles of three different heights (10%, 20% and 30% of leg length). Angular motions of the pelvis and lower limbs, and toe-obstacle clearances during leading- and trailing-limb crossings were calculated. Two-way analyses of variance were used to study between-subject (group) and within-subject (obstacle height) effects on the variables. Whenever a height effect was found, a polynomial test was used to determine the trend. A significance level of α = 0.05 was set for all tests. Results: Patients with MCI significantly increased pelvic anterior tilt, hip abduction and knee adduction in the swing limb during leading-limb crossing when compared to controls (p < 0.05). During trailing-limb crossing, the MCI group showed significantly decreased pelvic posterior tilt, as well as ankle dorsiflexion in the trailing swing limb (p < 0.05). Conclusions: Patients with MCI adopt altered kinematic strategies for successful obstacle-crossing. The patients were able to maintain normal leading and trailing toe-obstacle clearances for all tested obstacle heights with a specific kinematic strategy, namely increased pelvic anterior tilt, swing hip abduction and knee adduction during leading-limb crossing, and decreased pelvic posterior tilt and swing ankle dorsiflexion during trailing-limb crossing. The current results suggest that regular monitoring of obstacle-crossing kinematics for reduced toe-obstacle clearance or any signs of changes in crossing strategy may be helpful for early detection of compromised obstacle-crossing ability in patients with single-domain amnestic MCI. Further studies using a motor/cognitive dual-task approach on the kinematic strategies adopted by multiple-domain MCI will be needed for a complete picture of the functional adaptations in such a patient group.